IDENTIFIKASI ZAT LILIN PADA BUAH APEL YANG DIPERJUALBELIKAN DI PASAR PABAENG-BAENG KOTA MAKASSAR - Andi Auliyah Warsyidah; Jurnal Syarif; Mardawia DJ Samman (Jurnal Media Laboran, 2019)
This study aims to determine the presence or absence of waxes found in apples sold in Pabaeng-baeng market, Makassar City. Wax substances are additional ingredients that are used to coat the fruit so as not to quickly experience decay or damage. The type of this research is descriptive laboratory observations, namely to identify waxes in apples. This research was conducted on the 3rd of August 2018 at the DIII Laboratory of Health Analyst at the University of East Indonesia, Makassar City. The population in this study were all types of apples sold in the Pabaeng-baeng market in Makassar City with samples of 3 types of apples, each of which were green, red and reddish yellow. The variables in this study are apples and waxes. From the results of this study, it is known that there are waxes in 3 types of apples that are traded in the Pabaeng-baeng market in Makassar City